2023
DOI: 10.1101/2023.09.25.23296070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prenatal maternal infections and early childhood developmental outcomes: Analysis of linked administrative health data for Greater Glasgow & Clyde, Scotland

Iain Hardie,
Aja Murray,
Josiah King
et al.

Abstract: BackgroundPrevious research has linked prenatal maternal infections to later childhood developmental outcomes and socioemotional difficulties. However, existing studies have relied on retrospectively self-reported survey data, or data on hospital-recorded infections only, resulting in gaps in data collection.MethodsThis study used a large linked administrative health dataset, bringing together data from birth records, hospital records, prescriptions and routine child health reviews for 55,856 children born in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Maternal health during pregnancy plays an important role in shaping later childhood development, and there is now a growing body of evidence suggesting that prenatal maternal infections are associated with early childhood developmental outcomes. Previous research has found associations between maternal infections during pregnancy and reduced cognitive abilities [1, 2], emotional difficulties [3], health visitor developmental concerns [4] and a range of other developmental vulnerabilities [5] in children. There is also a large body of evidence linking prenatal maternal infections to childhood diagnoses of neurodevelopmental conditions such as autism [6-8] and attention-deficit/hyperactivity-disorder (ADHD) [9], as well as to adulthood mental health conditions including schizophrenia [10] and bipolar disorder [11].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal health during pregnancy plays an important role in shaping later childhood development, and there is now a growing body of evidence suggesting that prenatal maternal infections are associated with early childhood developmental outcomes. Previous research has found associations between maternal infections during pregnancy and reduced cognitive abilities [1, 2], emotional difficulties [3], health visitor developmental concerns [4] and a range of other developmental vulnerabilities [5] in children. There is also a large body of evidence linking prenatal maternal infections to childhood diagnoses of neurodevelopmental conditions such as autism [6-8] and attention-deficit/hyperactivity-disorder (ADHD) [9], as well as to adulthood mental health conditions including schizophrenia [10] and bipolar disorder [11].…”
Section: Introductionmentioning
confidence: 99%